2016
DOI: 10.1128/aac.02664-15
|View full text |Cite
|
Sign up to set email alerts
|

An Open, Randomized, Single-Center, Crossover Pharmacokinetic Study of Meropenem after Intraperitoneal and Intravenous Administration in Patients Receiving Automated Peritoneal Dialysis

Abstract: The objective of this study was to determine the pharmacokinetic profile of meropenem in automated peritoneal dialysis (APD) patients. In 6 patients without peritonitis, a single dose of 0.5 g of meropenem was applied intraperitoneally (i.p.) or intravenously (i.v.) and concentrations in serum and dialysate were measured at specified intervals over 24 h with high-performance liquid chromatography-mass spectrometry. The mean maximum concentrations of meropenem in serum (C max ) were 27.2 mg/ liter (standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Ratios of IP to systemic exposure indicated good systemic exposure after intraperitoneal application but limited penetration of the antibiotic into the peritoneal fluid after the intravenous dose. Similar results were reported by Wiesholzer et al (33) and Low et al (34). In 2006, A well designed prospective study of PK of cefepime by Elwell et al suggested that most APD and CAPD patients would achieve adequate serum cefepime concentrations if infused with a standard dose of 1,000 mg given IP (35).…”
Section: Discussionsupporting
confidence: 92%
“…Ratios of IP to systemic exposure indicated good systemic exposure after intraperitoneal application but limited penetration of the antibiotic into the peritoneal fluid after the intravenous dose. Similar results were reported by Wiesholzer et al (33) and Low et al (34). In 2006, A well designed prospective study of PK of cefepime by Elwell et al suggested that most APD and CAPD patients would achieve adequate serum cefepime concentrations if infused with a standard dose of 1,000 mg given IP (35).…”
Section: Discussionsupporting
confidence: 92%
“…For the measurement of plasma and intracellular AZM concentrations, a high performance liquid chromatography (HPLC)/triple quad mass spectrometry (MS) method was used ensuring selective and sensitive quanti cation of AZM levels (25)(26)(27). The HPLC/MS parameters were optimized for the detection of AZM and the internal standard erythromycin (ERM).…”
Section: Azm Level Measurementmentioning
confidence: 99%
“…The following sample preparation procedure was used: 100 µl of plasma or cell samples was mixed with 100 µl of a solution of the internal standard ERM and 600 µl of methanol were added, mixed and centrifuged at 15.000 rpm after 10 min., the supernatant (5 µl) was analysed by LC/MS. AZM was quanti ed using HPLC-MS/MS on an Ultimate 3000 RSLC-series system (Dionex, Germering, Germany) coupled to a triple quadrupole mass spectrometer (AB Sciex Instruments API 4000) equipped with an orthogonal ESI source operated in positive mode (25)(26)(27).…”
Section: Azm Level Measurementmentioning
confidence: 99%
“…Studies conducted in the APD population are only reserved to the parenteral administration of antibiotics in patients without peritonitis, yet vancomycin is primarily used to treat peritonitis and is mostly administered intraperitoneally. (27,28) With rapid cycling, the dialytic clearance of vancomycin may be increased. Therefore, if doses and dwell times used for those on the cycler are similar to those in CAPD, the result may be sub-therapeutic levels due to frequent exchanges.…”
Section: Automated Peritoneal Dialysismentioning
confidence: 99%